Spiritual Welfare in Elderly Al-Hikam Review Contributors at Al Ukhuwah Mosque Surabaya - Ahmad Khoirudin; Suryanto Suryanto; Dyan Evita Santi (International Conference on Psychology and Education (ICPE), 2023)
Spiritual well-being is a sense of harmony and closeness between oneself with others, nature and with the highest life. The purpose of this study is first to describe the spiritual well-being of the elderly, secondly to see how big the role of al-Hikam recitation is in improving the spiritual well-being of the elderly congregation. The subject of this research is the congregation of Al-Hikam recitation of Al-Ukhuwah Bendul Merisi Mosque. The research method used is qualitative with an intrinsic case study approach. The method of collecting is through interviews and observation. The results of spiritual welfare research with four aspects, namely indicating the harmony of the four dimensions in spiritual well-being that will bring happiness and harmony to individuals. Respondents can be said to be someone who has achieved spiritual well-being on the basis of relationships between the four domains that are well established as components of total and complete spiritual well-being. Elderly pilgrims can reduce all mental disorders that they feel as a process of entering old age. Disorders in the elderly generally are anxiety, anxiety, stress, because they feel no longer productive, reduced social and in the face of death. Good spiritual well-being can stem the disturbance that is present in the congregation. Through the study of the Al-Hikam book, elderly congregations can fix and improve spiritual welfare. So that the mentality of the elderly congregation is getting healthier and awake normally.